Coralline Algae at the Paleocene/Eocene Thermal Maximum in the Southern Pyrenees (N Spain) - Aguirre, Julio; Baceta, Juan I.; Braga, Juan C. (Frontiers in Marine Science, 2022)
During the Paleocene/Eocene Thermal Maximum, ~55.6 Ma, the Earth experienced the warmest event of the last 66 Ma due to a massive release of CO2. This event lasted for ~100 thousands of years with the consequent ocean acidification (estimated pH = 7.8-7.6). In this paper, we analyze the effects of this global environmental shift on coralline algal assemblages in the Campo and Serraduy sections, in the south-central Pyrenees (Huesca, N Spain), where the PETM is recorded within coastal-to-shallow marine carbonate and siliciclastic deposits. In both sections, coralline algae occur mostly as fragments, although rhodoliths and crusts coating other organisms are also frequent. Rhodoliths occur either dispersed or locally forming dense concentrations (rhodolith beds). Distichoplax biserialis and geniculate forms (mostly Jania nummulitica) of the order Corallinales dominated the algal assemblages followed by Sporolithales and Hapalidiales. Other representatives of Corallinales, namely Spongites, Lithoporella as well as Neogoniolithon, Karpathia, and Hydrolithon, are less abundant. Species composition does not change throughout the Paleocene/Eocene boundary but the relative abundance of coralline algae as components of the carbonate sediments underwent a reduction. They were abundant during the late Thanetian but became rare during the early Ypresian. This abundance decrease is due to a drastic change in the local paleoenvironmental conditions immediately after the boundary. A hardground at the top of the Thanetian carbonates was followed by continental sedimentation. After that, marine sedimentation resumed in shallow, very restricted lagoon and peritidal settings, where muddy carbonates rich in benthic foraminifera, e.g., milioliids (with abundant Alveolina) and soritids, and eventually stromatolites were deposited. These initial restricted conditions were unfavorable for coralline algae. Adverse conditions continued to the end of the study sections although coralline algae reappeared and were locally frequent in some beds, where they occurred associated with corals. In Serraduy, the marine reflooding was also accompanied by significant terrigenous supply, precluding algal development. Therefore, the observed changes in coralline algal assemblages during the PETM in the Pyrenees were most likely related to local paleoenvironmental shifts rather than to global oceanic or atmospheric alterations.